Educational-Entertainment and Healthy Lifestyle amongst Nigerian Youths: A Study of Select Episodes of Mtv Sugar - Ernest-Samuel, Gloria (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
The campaign for health education has been a major concern for government and non-governmental organizations. This has often times been carried out through the use of Theatrical performances-often referred to as Educational-Entertainment or Entertainment-Education. Among the campaign driven by Educational Entertainment, it has been observed that sex education for youths has often been neglected. The objective of this study is to determine how educational-entertainment can help to improve the healthy lifestyle among youths in Nigeria. To achieve this, the study uses simple percentages to analyze data collected for clarity of understanding and interpretation. To analyze the Episodes 3 and 4 of MTV Shuga Naija Season 1, 25 students were selected through random sampling to watch the episodes and were thereafter issued questionnaire that contained the questions raised for the research. The finding shows that 22 respondents agreed on the impact of the episodes viewed on their lives. Thus findings revealed that the edutainment programmes studied spurred the youths to adopt healthier lifestyles.